Management of menopausal women with a history of endometriosis - Elena I. Ermakova; Svetlana V. Yureneva (IP Berlin A.V., 2020)
Aim. To formulate a position statement on the management of the menopause in women with a past history of endometriosis from the point of view of evidence-based medicine. Materials and methods. Review of domestic and foreign literature, position of IMS and EMAS. Results. The article describes the main modes snd ways of introducing MHT and their advantages. The expert position on the management of patients with a history of endometriosis during surgical and natural menopause is highlighted. Information on the prevalence and methods of treatment of postmenopausal endometriosis is given.